Antimicrobial action of sodium hypochlorite and castor oil solutions for denture cleaning - in vitro evaluation - Marcela Moreira SALLES; Viviane de Cássia OLIVEIRA; Raphael Freitas SOUZA; Cláudia Helena Lovato SILVA; Helena de Freitas Oliveira PARANHOS (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objective of this in vitro study was to evaluate the antimicrobial action of sodium hypochlorite (0.25% and 0.50%) and 10% castor oil solutions against specific microorganisms, by counting Colony Forming Units (CFU) of clinically important bacteria and Candida species. Acrylic resin specimens (n = 320; Lucitone 550) were obtained from square metal matrices (10 x 10 x 2 mm), sterilized by microwave (650W, for 6 minutes) and contaminated by Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, Bacillus subtilis, Escherichia coli, Streptococcus mutans, Enterococcus faecalisand Candida glabrata. The specimens were immersed for 20 minutes in one of the following hygiene solutions (n = 10/each): A - 0.25% Sodium hypochlorite; B - 0.5% Sodium hypochlorite; C - 10% Castor oil solution; and D (Control) - saline. Adhered cells were suspended and inoculated into a selective solid medium (37ºC for 24 h). The Student's t-test (α = 0.05) was performed to compare log10(CFU+1)/mL between Groups C and D. The results showed that sodium hypochlorite (0.25% and 0.5%) completely eliminated all detectable microorganisms. The castor oil solution eliminatedB. subtilisand reduced counts for other strains. Differences between C and D were significant (p < 0.05) for all species except for E. faecalis. Both sodium hypochlorite solutions (0.25% and 0.5%) were effective in eliminating all microorganisms evaluated, and may be useful as cleaning solutions for complete dentures. The castor oil solution provided moderate efficacy and performed differently on the tested species, with the strongest effect on B. subtilis and with non-significant action on E. faecalis.